2009
DOI: 10.1017/s1368980008003704
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of fortification of corn flour-derived products with hydrogen-reduced elemental iron on iron-deficiency anaemia in children and adolescents in southern Brazil

Abstract: Objective: To find the ideal combination of Fe fortifier and its food vehicle is an essential measure in developing countries. However, its cost also plays an important role. In the present study, the effect on blood parameter values of corn flour-derived products fortified with powdered elemental Fe in the form of H 2 -reduced Fe was investigated in children and adolescents. Methods: One hundred and sixty-two individuals (eighty-six boys and seventy-six girls) from public educational centres in Londrina, Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
3
0
5
Order By: Relevance
“…Of these, 121 [25-145] studies were on infants and children and 79 [146-224] were on women, while one study had both women and children as their study population [33] (Figure 2). Furthermore 125 [25-28,30,32-39,41-44,47,48,51,53],[54,56,59,60,62,63,65-73,75-77],[81-83,85,86,88-90,92,93,95-104,107-109],[111-117,119-127,129,130,132-136,139-144,223,225-228] of these trials were RCTs; the rest were quasi-experimental [46,55,61,74,78,87,91] and before-after studies [29,31,40,45,49,50,52,57],[58,79,80,84,94,95,105,131],[137,138,149,150,153,157,159-169,172],[174,177,181,183-186,189-191,193,195-…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 121 [25-145] studies were on infants and children and 79 [146-224] were on women, while one study had both women and children as their study population [33] (Figure 2). Furthermore 125 [25-28,30,32-39,41-44,47,48,51,53],[54,56,59,60,62,63,65-73,75-77],[81-83,85,86,88-90,92,93,95-104,107-109],[111-117,119-127,129,130,132-136,139-144,223,225-228] of these trials were RCTs; the rest were quasi-experimental [46,55,61,74,78,87,91] and before-after studies [29,31,40,45,49,50,52,57],[58,79,80,84,94,95,105,131],[137,138,149,150,153,157,159-169,172],[174,177,181,183-186,189-191,193,195-…”
Section: Resultsmentioning
confidence: 99%
“…A total of 41 [25,26,28,30-32,35,39,48,49],[54,56,57,65,70,77,80,81],[83,85,88,89,97,99,101,104],[106-108,112-114,116,120,124,126],[127,129,135,136,139] studies reported outcomes for impact of iron fortification. Four of the studies were before-after studies and the rest were RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Nutrients are often added in combinations, but nutritional improvements can be achieved using single nutrients. For example, maize flour fortified with powdered iron (as Fe(II)) decreased iron deficiency and iron‐related anemia in Brazilian children and adolescents in 6 mo (Miglioranza and others 2009). Adding folic acid to U.S. maize flour at 140 μg/100 g, effectively increased Mexican American women's intake by 20%.…”
Section: Current Trends In Improving Nutritional Quality Of Maizementioning
confidence: 99%
“…Özellikle çocukluk döneminde geliflme ve büyümeye olumsuz etkiler yapt›¤› iyi bilinmektedir (2)(3)(4). Bu olumsuz etkilerden korunmak için 4 ay-1 yafl aras› bebeklere koruyucu dozda demir verilmesi gerekti¤i önerilmektedir (5).…”
Section: Giriflunclassified
“…Baz› çal›flmalarda ise koruyucu demir verilmesinin alt›nc› aydan bafllanarak dokuzuncu aya kadar devam edilmesi gerekti¤i belirtilmektedir (18 Bizim çal›flmam›z dördüncü ay sonras›nda koruyucu doz demir verilmesi gerekti¤i tezini desteklemektedir. Ayr›ca Amerikan Çocuk Akademisi de bebeklere dördüncü aydan itibaren 1 mg/kg/gün demir deste¤i verilmesini önermektedir (2)(3)(4). Ancak ebeveynler demir ilac›n› vermeyi ya unutmakta, ya önemsememekte ya da her gün vermek aile için s›k›nt› verebilmektedir.…”
Section: Tart›flmaunclassified